Therapy resistance in neuroblastoma: Mechanisms and reversal strategies - Zhou, Xia; Wang, Xiaokang; Li, Nan; Guo, Yu; Yang, Xiaolin; Lei, Yuhe (Frontiers in Pharmacology, 2023)
Neuroblastoma is one of the most common pediatric solid tumors that threaten the health of children, accounting for about 15% of childhood cancer-related mortality in the United States. Currently, multiple therapies have been developed and applied in clinic to treat neuroblastoma including chemotherapy, radiotherapy, targeted therapy, and immunotherapy. However, the resistance to therapies is inevitable following long-term treatment, leading to treatment failure and cancer relapse. Hence, to understand the mechanisms of therapy resistance and discover reversal strategies have become an urgent task. Recent studies have demonstrated numerous genetic alterations and dysfunctional pathways related to neuroblastoma resistance. These molecular signatures may be potential targets to combat refractory neuroblastoma. A number of novel interventions for neuroblastoma patients have been developed based on these targets. In this review, we focus on the complicated mechanisms of therapy resistance and the potential targets such as ATP-binding cassette transporters, long noncoding RNAs, microRNAs, autophagy, cancer stem cells, and extracellular vesicles. On this basis, we summarized recent studies on the reversal strategies to overcome therapy resistance of neuroblastoma such as targeting ABC transporters, MYCN gene, cancer stem cells, hypoxia, and autophagy. This review aims to provide novel insight in how to improve the therapy efficacy against resistant neuroblastoma, which may shed light on the future directions that would enhance the treatment outcomes and prolong the survival of patients with neuroblastoma.